Heart of a warrior - Lindsey, Johanna (New York : William Morrow, 2001)
Independent California woman Brittany Callaghan struggles with her attraction to the handsome barbarian warrior who shows up on her doorstep, seeking her as a lifemate.
Keywords: Man-woman relationships -- Fiction; Man-woman relationship -- Fiction; Fantasy fiction; Love stories; California -- Fiction; California -- Fiction; Fantasy fiction; Love stories